2017
DOI: 10.1093/hmg/ddw418
|View full text |Cite
|
Sign up to set email alerts
|

Parkin functionally interacts with PGC-1α to preserve mitochondria and protect dopaminergic neurons

Abstract: To understand the cause of Parkinson's disease (PD), it is important to determine the functional interactions between factors linked to the disease. Parkin is associated with autosomal recessive early-onset PD, and controls the transcription of PGC-1α, a master regulator of mitochondrial biogenesis. These two factors functionally interact to regulate the turnover and quality of mitochondria, by increasing both mitophagic activity and mitochondria biogenesis. In cortical neurons, co-expressing PGC-1α and Parkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 72 publications
3
63
0
Order By: Relevance
“…Mfn2 is a key ubiquitination target of Parkin (Matsuda et al, 2010;Nguyen, Padman & Lazarou, 2016), and Parkin mediates the expression of PGC-1α (Shin et al, 2011), which in turn controls Mfn2 expression under stress conditions (see Section IV) (Bach et al, 2003Soriano et al, 2006). Under healthy conditions, Parkin has been proposed to protect dopaminergic neurons by promoting mitochondrial homeostasis in a PGC-1α-dependent manner (Zheng et al, 2017). Furthermore, Mfn2 has been reported to function as a receptor for Parkin in cardiac cells (Chen & Dorn, 2013;Gong et al, 2015), however whether this extends beyond this cell type is unclear (Narendra et al, 2008;Nguyen et al, 2016).…”
Section: (2) Additional Neurodegenerative Diseasesmentioning
confidence: 99%
“…Mfn2 is a key ubiquitination target of Parkin (Matsuda et al, 2010;Nguyen, Padman & Lazarou, 2016), and Parkin mediates the expression of PGC-1α (Shin et al, 2011), which in turn controls Mfn2 expression under stress conditions (see Section IV) (Bach et al, 2003Soriano et al, 2006). Under healthy conditions, Parkin has been proposed to protect dopaminergic neurons by promoting mitochondrial homeostasis in a PGC-1α-dependent manner (Zheng et al, 2017). Furthermore, Mfn2 has been reported to function as a receptor for Parkin in cardiac cells (Chen & Dorn, 2013;Gong et al, 2015), however whether this extends beyond this cell type is unclear (Narendra et al, 2008;Nguyen et al, 2016).…”
Section: (2) Additional Neurodegenerative Diseasesmentioning
confidence: 99%
“…In the first one, Cali et al showed that overexpression of Parkin in neuroblastoma cells increases ER-mitochondria juxtaposition, and enhances IP 3 R-dependent mitochondrial Ca 2+ transients and ATP production; Parkin down-regulation by RNA interference has the opposite effect . Parkin overexpression in nigral neurons also led to a slight increase in the percentage of mitochondria in contact with the ER (Zheng et al, 2017). In contrast, we and others recently associated Parkin and PINK1 dysfunction with an exacerbation of the ER-mitochondria interface (Celardo et al, 2016;Gautier et al, 2016).…”
Section: Parkinson's Diseasementioning
confidence: 53%
“…Of note, Parkin has recently been reported to co-regulate ER-mitochondria juxtaposition together with the transcription factor peroxisome proliferator-activated receptor γ coactivator 1α (PGC1α), a key modulator of mitochondrial biogenesis (Zheng et al, 2017). In this study, the overexpression of PGC1α in the mouse substantia nigra by means of an adeno-associated viral vector led to exacerbation of ERmitochondria contacts that was suppressed by the co-expression of Parkin.…”
Section: Parkinson's Diseasementioning
confidence: 82%
See 2 more Smart Citations